The use of a long-acting tranquilizer (zuclopenthixol acetate) and live video monitoring for successful long-distance transport of caribou (Rangifer tarandus) - Owen Slater (Septentrio Academic Publishing, 2021)
Long-distance transport of caribou (Rangifer tarandus) can result in morbidities and mortalities. This case report describes the use of a long-acting tranquilizer, zuclopenthixol acetate (ZA) and live video monitoring (LVM) to transport caribou over 2300 kilometers. Two groups of captive caribou were transported from Fort St. John, British Columbia to Dryden, Ontario (n=14; 28.5 h transport) and Anchorage, Alaska (n=11; 32 h transport).  The day prior to transport, caribou were administered ZA at 1 mg/kg via deep intramuscular (IM) injection.  Digital video cameras allowed for live observation of caribou during transport.  Still images of videos from each compartment in the Ontario transport were analyzed for percentage (%) lying versus standing over three time periods (Day 1, Night, and Day 2).  Overall, caribou spent 57% of the transport lying down, with the highest percentage occurring at night (73%).  As group size and animal density decreased there was a trend for caribou to spend more time lying down.  Three animals developed extrapyramidal effects to the ZA and were effectively treated with midazolam at 0.2 mg/kg IM. There were no significant visible injuries or mortalities during or up to 6 weeks post-transport. Zuclopenthixol acetate and LVM were used to successfully transport  caribou over long distances and should be considered in future translocations to improve animal welfare during transport.